Effects of Organic and Inorganic Fertilizers on Growth and Nutrient Uptake by Young Cacao (Theobroma cacao L.) - Jerome A. Dogbatse; Alfred Arthur; Godfred K. Awudzi; Amos K. Quaye; Sampson Konlan; Andrews A. Amaning (International Journal of Agronomy)
Sustainable cacao cultivation in Ghana has been seriously hampered by high seedling mortality due to the low soil fertility of lands used for the establishment of new cacao farms. Alleviating the low soil fertility to enhance sustainable cacao cultivation requires the use of fertilizers. A study was therefore conducted at the Cocoa Research Institute of Ghana to determine the effect of integrated application of poultry manure (PM) and sulphate of ammonia (SOA) fertilizers on survival, growth, and nutrient uptake by cacao seedlings under marginal field conditions. A randomized complete block design with four replications was used to evaluate the effects of six treatments. Traits assessed were percentage survival, height, trunk cross-sectional area (TCSA), and nutrient uptake. Results from the study showed no significant differences in soil N and K among the treatments. PM-amended plots had significantly higher soil P than nonamended control and SOA alone. Seedling survival rate ranged from 73.3 to 89.3% with a higher proportion of surviving plants in PM amended soils. The application of PM alone and its combination with SOA improved growth. Cacao trees of T4 (75% recommended dosage of SOA + PM) had the largest TCSA increment, which was significantly different from the other soil treatments. Leaf nutrient concentrations in cacao of T4 were higher than the other soil treatments. It was therefore concluded that T4 could be used during cacao establishment in marginal areas for improved plant survival and growth.